2018
DOI: 10.1007/978-3-319-74412-4_7
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Community Structure in Dynamic Social Networks Using the Concept of Leadership

Abstract: Abstract-Detecting community structure in social networks is a fundamental problem empowering us to identify groups of actors with similar interests. There have been extensive works focusing on finding communities in static networks, however, in reality, due to dynamic nature of social networks, they are evolving continuously. Ignoring the dynamic aspect of social networks, neither allows us to capture evolutionary behavior of the network nor to predict the future status of individuals. Aside from being dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…However, how can the interaction information be advanced to create a populous cooperation structure? Accounting for the possible interactions between individual users of a network, emphasizing selective neighbor interactions, can lead to natural reward and cooperation, in line with the game theory model [9,10]. This conditional reward, in accordance with the game theory model, encourages interactions that produce a clustering strategy, known as local interactions with non-random cooperation.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, how can the interaction information be advanced to create a populous cooperation structure? Accounting for the possible interactions between individual users of a network, emphasizing selective neighbor interactions, can lead to natural reward and cooperation, in line with the game theory model [9,10]. This conditional reward, in accordance with the game theory model, encourages interactions that produce a clustering strategy, known as local interactions with non-random cooperation.…”
Section: Introductionmentioning
confidence: 82%
“…When individuals collaborate to support each other, they both save and spend money in the process. Cooperation is a vital component of any human community network [1][2][3][4][9][10][11][12][13]. Accumulating evidence suggests that people are impacted by their social connections, spreading emotions, beliefs, and behaviors throughout their networks [15][16][17][18][19][20][21][22][23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this regard, it is not a suitable approach. Similarly, Javadi et al [33] introduced a local community detection method that is based on the leadership concept. In this study, the leaders were identified over a certain time in the first step.…”
Section: Related Workmentioning
confidence: 99%
“…Evaluation metrics for dynamic graphs must necessarily take into account also the temporal aspect other than the simple distance between nodes. Several variations of the metrics in use for static graphs (such as Modularity, Conductance and Expansion) have been adapted to evaluate the goodness of the clusters in dynamic graphs [47]. Most of such techniques consider the measure that characterize the cluster at the next snapshot with respect to its variation to the current one, providing effective solutions to test the community discovery technique in use.…”
Section: Properties Of Communitiesmentioning
confidence: 99%